Mosquito-borne West Nile virus (WNV) surveillance in the Upper Rhine Valley, Germany - Timmermann, Ute; Becker, Norbert (Journal of vector ecology, 2010)
ABSTRACT: West Nile virus (WNV) could be introduced into Germany via migratory birds originating from Africa or southern Europe and subsequently transmitted to indigenous birds, humans, or horses by mosquitoes. Neither the virus itself nor antibodies against WNV have yet to be found in mosquitoes and horses, whereas antibodies have been detected in migrating birds and in humans that were in close contact with birds. At present, the West Nile virus itself has yet to be detected in Germany. This investigation was conducted primarily in major bird breeding, resting, and roosting habitats (hotspots) in the Upper Rhine Valley. Adult mosquitoes were trapped using CO2-baited Encephalitis Vector Surveillance (EVS)-traps and were tested for WNV by the VecTest WNV Antigen Assay. In 2007 and 2008, a total of 11,073 host-seeking adult female mosquitoes (13 species) were tested, and all tests were negative for WNV. Statistical calculations could be performed only where sufficient numbers of mosquitoes were trapped. For these sites, WNV infection among mosquitoes could be ruled out with 80% certainty. For the evaluation of the WNV situation in Germany, the results of this investigation are a further indication that the virus has not yet arrived.